Pengaruh Ketebalan Mulsa Organik Ki Rinyuh (Chromolaena Odorata) Terhadap Produksi Bahan Segar, Bahan Kering dan Bahan Organik Rumput Gajah Mini (Pennisetum Purpureum Cv. Mott) - Jaiman, Rista; Temu, Stefanus Tany; Osa, Dominggus Benyamin (Yayasan Sumber Daya Manusia Cerdas, 2025)
This research was conducted at the Archipelagic Dry Land Integrated Field Laboratory, Nusa Cendana University, Kelapa Lima District, Kupang City, Lasiana Village for 3 months, from march to june 2022. The purpose of this study was to determine the effect of the thickness of kirinyuh Organic mulch (Chromolaena odorata) on production Fresh matter, dry matter and organic matter mini elephant grass (Pennisetum purpureum cv. Mott), soil and organic ki rinyuh mulch (Chromolaena odorata) the method used was a Randomized Block Design (RAK) consisting of 4 treatments and 4 replications. The treatments studied were as follows M0 = no mulch (control),, M1 = 1 cm thick mulch, M2 = 3 cm thick mulch, M3 = 5 cm thick mulch The data were analyzed using variance (ANOVA) and continued with Duncan's test. The results of variance showed that the treatment had no significant effect (P˃0,05) on the production of fresh matter, dry matter, and organic matter of mini elephant grass (Pennisetum purpureum cv. Mott). The conclusion is that ki rinyuh organic mulch (Chromolaena odorata) with a thickness of 3 cm gives the highest response to the production of fresh material (3,911 kg/m^2), dry matter production (29,525 kg/m^2), and organic matter production (161,868 g/m^2) mini elephant grass (Pennisetum purpureum cv. Mott).